PENGARUH PIJAT OKSITOSIN TERHADAP PRODUKSI ASI PADA IBU DENGAN BBLR DI RUANG NICU RSUD TAMAN HUSADA BONTANG - Yantigustina; Andi Lis Arming Gandini; Sutrisno Sutrisno (Jurnal Cakrawala Ilmiah, 2023)
Introduction: Oxytocin massage can increase breast milk production in postpartum mothers with low birth weight (LBW) babies in the NICU. Oxytocin massage is performed along the spine (vertebrae) to the fifth-sixth costae bone, and is an attempt to stimulate prolactin and oxytocin hormones. Methods: Correlational design with quasy experimental design with control group. Population of all breastfeeding mothers with LBW in the NICU room. The sampling method was probability random sampling of 20 people, which was divided into an intervention group of 10 people and a control group of 10 people. Instruments used demographic data questionnaires and breast milk production observation sheets. Data analysis used frequency distribution and percentage and Mann Whitney U Test statistical test. Results: Results: Wilcoxon test with p-value=0.002 (p-value<0.05) which means there is a difference in breast milk production before and after giving oxytocin massage to LBW mothers in the intervention group. The Wilcoxon test p-value = 0.083 (p-value> 0.05) means there is no difference in breast milk production before and after the 15th day without giving oxytocin massage to LBW mothers in the control group. The results of the Mann-WhitneyU statistical test obtained a p-value = 0.004 (p-value <0.05), which means that there is an effect of oxytocin massage on breast milk production in LBW mothers. Conclusion: There is an effect of oxytocin massage on breast milk production in mothers with LBW in the NICU Room of RSUD Taman Husada Bontang. Keywords: oxytocin massage, breast milk production, mothers with LBW, NICU Room